2020
DOI: 10.1038/s41598-020-76561-w
|View full text |Cite
|
Sign up to set email alerts
|

Deacidification by FhlA-dependent hydrogenase is involved in urease activity and urinary stone formation in uropathogenic Proteus mirabilis

Abstract: Proteus mirabilis is an important uropathogen, featured with urinary stone formation. Formate hydrogenlyase (FHL), consisting of formate dehydrogenase H and hydrogenase for converting proton to hydrogen, has been implicated in virulence. In this study, we investigated the role of P. mirabilis FHL hydrogenase and the FHL activator, FhlA. fhlA and hyfG (encoding hydrogenase large subunit) displayed a defect in acid resistance. fhlA and hyfG mutants displayed a delay in medium deacidification compared to wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Both the Hyb and Hyf [NiFe] hydrogenases are thought to contribute to membrane potential and proton motive force in other bacterial species (Schoelmerich & Müller, 2020, Vignais & Billoud, 2007. In agreement with this hypothesis, Lin et al reported that the Hyf system contributes to P. mirabilis acid tolerance (Lin & Liaw, 2020), which we have found to be a reliable surrogate for assessing alterations in membrane potential (Armbruster et al , 2014, Brauer et al , 2022. We therefore sought to determine the contribution of each hydrogenase to acid tolerance in P. mirabilis strain HI4320.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Both the Hyb and Hyf [NiFe] hydrogenases are thought to contribute to membrane potential and proton motive force in other bacterial species (Schoelmerich & Müller, 2020, Vignais & Billoud, 2007. In agreement with this hypothesis, Lin et al reported that the Hyf system contributes to P. mirabilis acid tolerance (Lin & Liaw, 2020), which we have found to be a reliable surrogate for assessing alterations in membrane potential (Armbruster et al , 2014, Brauer et al , 2022. We therefore sought to determine the contribution of each hydrogenase to acid tolerance in P. mirabilis strain HI4320.…”
Section: Resultssupporting
confidence: 55%
“…[NiFe] hydrogenases do not contribute to urease activity,acid tolerance, or motility in P. mirabilis strain HI4320 . Lin et al previously demonstrated that the Hyf system contributes to optimal urease activity of P. mirabilis at low pH (Lin & Liaw, 2020). Specifically, disrupting hyfG in P. mirabilis strain N2 largely resulted in decreased urease activity in synthetic urine at acidic to neutral pH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteus mirabilis is the third most common pathogen which is isolated (after Escherichia coli and Klebsiella pneumonia) from urinary tract infections. It also is the leading cause bacterium in catheter-associated urinary tract infections (CAUTI) that usually associated with formation of urinary stones and the obstruction of urinary catheters [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The [NiFe] hydrogenases in pathogenic bacteria have been classified into at least 13 subgroups based on properties such as their genetic organization, localization, redox partners, oxygen tolerance, and activity [17][18][19]. P. mirabilis HI4320 encodes two putative [NiFe] hydrogenases: a Hyb-type Group 1c hydrogenase predicted to oxidize H 2 and generate PMF through respiration of fumarate or other highpotential oxidants [20], and a Hyf-type Group 4a hydrogenase that was recently confirmed to contribute to P. mirabilis acid tolerance through formate-dependent production of H 2 [21].…”
Section: Introductionmentioning
confidence: 99%